Red blood cell vesiculation in hereditary hemolytic anemia - Alaarg, Amr; Schiffelers, Raymond; van Solinge, Wouter W.; Van Wijk, Richard (Frontiers in Physiology, 2013)
Hereditary hemolytic anemia encompasses a heterogeneous group of anemias characterised by decreased red blood cell survival because of inherited membrane, enzyme, or hemoglobin disorders. Affected red blood cells are more fragile, less deformable, and more susceptible to shear stress and oxidative damage, and show increased vesiculation. Red blood cells, as essentially all cells, constitutively release phospholipid extracellular vesicles in vivo and in vitro in a process known as vesiculation. These extracellular vesicles comprise a heterogeneous group of vesicles of different sizes and intracellular origins. They are described in literature as exosomes if they originate from multi-vesicular bodies, or as microvesicles when formed by a one-step budding process directly from the plasma membrane. Extracellular vesicles contain a multitude of bioactive molecules that are implicated in intercellular communication and in different biological and pathophysiological processes. Mature red blood cells release in principle only microvesicles. In hereditary hemolytic anemias, the underlying molecular defect affects and determines red blood cell vesiculation, resulting in shedding microvesicles of different compositions and concentrations. Despite extensive research into red blood cell biochemistry and physiology, little is known about red cell deformability and vesiculation in hereditary hemolytic anemias, and the associated pathophysiological role is incompletely asessed. In this review, we discuss recent progress in understanding extracellular vesicles biology, with focus on red blood cell vesiculation. Also, we review recent scientific findings on the molecular defects of hereditary hemolytic anemias, and their correlation with red blood cell deformability and vesiculation. Integrating bio-analytical findings on abnormalities of red blood cells and their microvesicles will be critical for a better understanding of the pathophysiology of hereditary hemolytic anemias.